Mitochondrial diabetes and its lessons for common Type 2 diabetes. (25th October 2006) - Maassen, J.A.; 't Hart, L.M.; Janssen, G.M.C.; Reiling, E.; Romijn, J.A.; Lemkes, H.H.
Abstract : Multiple pathogenic pathways are able to deregulate glucose homoeostasis leading to diabetes. The 3243A>G mutation in the mtDNA (mitochondrial DNA)-encoded tRNA Leu, UUR gene was found by us to be associated with a particular diabetic subtype, designated MIDD (maternally inherited diabetes and deafness). This mutation causes an imbalance in the mitochondrion between proteins encoded by the nuclear and mitochondrial genomes, resulting in a gradual deterioration of glucose homoeostasis during life. Remarkably, carriers of the 3243A>G mutation are generally not obese. The mutation also results in enhanced radical production by mitochondria. We propose that this mutation leads to the development of diabetes due to an inappropriate storage of triacylglycerols within adipocytes. The result is a fatty acid-induced deterioration of pancreatic β-cell function. In combination with an enhanced radical production in the β-cell due to the mutation, this leads to an age-dependent, accelerated decline in insulin production. In common Type 2 (non-insulin-dependent) diabetes, which is generally associated with obesity, a decline in mitochondrial function in adipose cells seems to result in an inappropriate scavenging of fatty acids by β-oxidation. As a consequence, a systemic overload with fatty acids occurs, leading to an enhanced decline in β-cell function due to lipotoxicity.